Influence of Protein Intake from Haem and Non-haem Animals and Plant Origin on Inflammatory Biomarkers among Apparently-healthy Adults in Greece (Journal of Health, Population and Nutrition, 2014)
Intake of different types of protein may be associated with differences in biomarkers among various populations. This work investigated the influence of protein intake from haem and non-haem animals as well as protein from plants on haematological and biochemical parameters in inflammation among apparentlyhealthy adults living in Greece, a Mediterranean country. Four hundred and ninety apparently-healthy subjects (46±16 years, 40% men), who consecutively visited Polykliniki General Hospital for routine examinations, voluntarily agreed to participate in the study (participation rate 85%). Demographic, anthropometric and lifestyle characteristics were recorded. Participants completed a valid, semi-quantitative food frequency questionnaire. Protein intake was classified into three sources: protein from haem animals, protein from non-haem animals, and protein from plant origin. Fasting blood samples were taken from all participants; uric acid, creatinine, lipids, cystatin C, haptoglobin, haemoglobin, haematocrit, iron, ferritin, white blood cells, monocytes, platelets, and C-reactive protein were measured. Protein intake from only haem animals was associated with increased haemoglobin and haematocrit levels (p